Relaxation channels and transfer of energy stored by pre-irradiated rare gas solids - Savchenko, E.V.; Khyzhniy, I.V.; Uyutnov, S.A.; Gumenchuk, G.B.; Ponomaryov, A.N.; Bondybey, V.E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
The processes of energy relaxation in rare gas solids pre-irradiated with an electron beam are discussed. We studied the emission of exoelectrons and photons from RGS. Investigations were performed by a set of activation spectroscopy methods applied simultaneously to each sample. Photon-stimulated exoelectron emission from solid Ne was observed for the first time.